Clinical implications of troponin-T elevations following TAVR: Troponin Increase Following TAVR. Issue 2 (February 2022) - Imamura, Teruhiko; Oshima, Akira; Narang, Nikhil; Onoda, Hiroshi; Tanaka, Shuhei; Ushijima, Ryuichi; Sobajima, Mitsuo; Fukuda, Nobuyuki; Ueno, Hiroshi; Kinugawa, Koichiro
Highlights: Troponin-T increases following transcatheter aortic valve replacement in 40% of patients. Post-procedural increase in troponin-T is associated with in-hospital atrio-ventricular block. Post-procedural increase in troponin-T is also associated with long-term prognosis. Abstract: Background: Baseline and post-procedural elevations in serum troponin-T levels are associated with increased morbidity and mortality following transcatheter aortic valve replacement (TAVR). However, the prognostic impact of change in serum troponin-T level following TAVR remains unknown. Methods: Among the patients with severe aortic stenosis who underwent TAVR, those with baseline serum troponin-T level ≥51.5 ng/L were excluded. The impact of increases in serum troponin-T level to an abnormally high range (≥51.5 ng/L) following TAVR on 2-year cardiovascular death or heart failure readmissions was investigated. Results: Among 189 included patients (median 86 years old, 28% men), serum troponin-T level increased in 79 patients following TAVR. An increase in serum troponin-T was associated with a higher rate of 30-day adverse events, predominantly due to pacemaker implantation for complete atrio-ventricular block, and a higher 2-year cumulative incidence of the primary endpoint (hazard ratio 5.24, 95% confidence interval 1.64-16.8, p = 0.005) adjusted for the potential confounders. Conclusion: Post-procedural increase in serum troponin-T level was associated with adverse clinical outcomes following TAVR. Graphical abstract: Image, graphical abstract